The mitogenomes of three beetles (Coleoptera: Polyphaga: Cucujiformia): New gene rearrangement and phylogeny. (December 2016) - Li, Xuejuan; Ou, Jing; Wei, Zhaoming; Li, Yaxiao; Tian, Yingfang
Abstract: The mitochondrial genome (mitogenome) has been extensively used for studying phylogenetic relationships at different taxonomic levels. Several molecular analyses have been performed, but the phylogenetic relationships among infraorders in Polyphaga have not been well resolved. In this work, three nearly complete mitogenomes of Coleoptera, Sitophilus oryzae, Oryzaephilus surinamensis and Callosobruchus chinensis, were determined. The O. surinamensis and S. oryzae mitogenomes harbor gene content typical of other Polyphaga mitogenomes, while a gene rearrangement (trnQ) was found in the C. chinensis mitogenome. The mitogenomes of these three Coleoptera species each consist of approximately 13 protein-coding genes, 22 tRNA genes, two rRNA genes and one A + T-rich region. Phylogenetic analysis within Polyphaga was carried out based on mitochondrial data. The phylogenetic results within Polyphaga support the basal position of Cyphon sp., which belonged to Scirtoidea, Elateriformia. Within Cucujiformia, monophyletic Curculionoidea, Chrysomeloidea and Tenebrionoidea were confirmed. Highlights: Three nearly complete mitogenomes of Coleoptera were sequenced. A new gene rearrangement was found in Callosobruchus chinensis. Some phylogenetic relationships within Polyphaga were confirmed.